Dėl indoeuropiečių „ugnies“ vardų - Mažiulis, Vytautas (Baltistica, 2008)
The Indo-Europeans used ‘fire’ in two main meanings: a) ‘hearth (→ camp) fire’ (‘I fire’) and b) ‘lightening-thunder (→ blaze) fire’ (‘II fire’). Both I.-E. fires are taboo, especially ‘II fire’; this is why it was very open to euphemism and mythologisation. It seems, that both I.-E. fire names later experienced certain contaminations in dialects, in some places reflected by ‘I fire’, and elsewhere by ‘II fire’. The archaic Lith. ugnìs (= Latv. *ugnis) most likely derives from I.-E. *n̥gni-, which gave rise to b.-sl. *ungnis, turning this into b.-sl. *ugnis (> Lith. ugnìs, etc.) due to the loss of the root’s nasality from alliteral dissimilation (AD). The AD rule influenced not only Baltic and Slavic words, but other Indo-European words with root alliteration. The I.-E. * n̥gni- (‘I fire’) is most likely linked with I.-E. *angli- ‘hearth (ember) fire’ having the apophonic root I.-E. *ang- (> Lith. anglìs ‘coal’, etc.). They can both presuppose the ‘I fire’ synonymous heteroclit forms n̥g-i/n-and *ang-i/l-, which are derived from heteroclit I.-E. forms of non I.-E. verb. * n̥g-//*ang-. The component titi- of the Lith. (dial.) compound titi-nagas and component Tit- of Lith. hydronyms quite clearly presupposes the I.-E. ‘II fire’ heteroclit *titi-, which is a derivative of the I.-E. formant *-i/n- from non I.-E. verb. *tit-, meaning ‘to gleam (to lighten)’. It seems that the the above-mentioned I-E. ‘II fire’ was older than I.-E. r/n- heteroclit ‘II fire’, which due to its strong taboo was euphemistically reworked from *peHur- /*peHun- to *peHnu- (metathesis) > *penu- > West Balt. *panu ‘fire’.